Effects of ambient density and high injection pressure on the flow characteristics of biodiesel spray - Mohd Yaacob, Nur Syuhada; Khalid, Amir; Nursal, Ridwan Saputra; Jaat, Norrizam; Andsaler, Adiba Rhaodah; Azizul, Muhamad Asri; Manshoor, Bukhari; Zaman, Izzuddin (2024)
Fuel spray and mixture formation are playing as an important criteria in displaying a fuel's combustion and emission characteristics since it has an instantaneous impact on the creation of an air fuel combination. The purpose of this study is to compare the effects of three different Crude Palm Oil (CPO) biodiesel blends, B5, B10, and B15, with different ambient density on nozzle flow and spray characteristics, computational fluid dynamics (CFD) were used to determine the nozzle flow and spray characteristics for different injection pressure of biodiesel spray to ambient variant conditions on mixture formation. Injection of biodiesel into the RCM constant volume chamber was considered in the simulation. While maintaining constant values for the other parameters, the boundary condition is adjusted at a different ambient parameter. Under the presence of in-cylinder flow, the impact of fuel type, injection pressure, and ambient variables on spray behaviour, such as spray penetration, has been explored. It was projected that high injection pressures would be more essential for the biodiesel fuels to develop their breakup. The effects of these various parameters are examined in terms of spray characteristics and opposed with the results of the experiment